THE USE OF TIKTOK APPLICATION FOR DESCRIPTIVE TEXT IN ENGLISH WRITING FOR THE TENTH GRADE OF VOCATIOANAL HIGH SCHOOL - Sonia Virgin, Elsa; Nur Affini, Laily (Jurnal Ilmiah Spectral, 2022)
This study aims to discover the benefits of using the Tik-Tok application in writing descriptive text. Then, find out if the Tik-Tok application helps students write and solve problems they find while writing. The purpose of this survey is the result of a 10th- grade study at SMK Yatpi Godong. SMK Yatpi Godong has 32 10th graders. In this case, researchers used a questionnaire that consisted of open-form questions to collect survey data. This study used qualitative research, and the data was collected using words and photographs rather than numbers. The researchers occupied open-form questions to get information from students and then changed the survey results to percentages. Last, examining and interpreting all the data. From the impact of the data analysis, 86,36% of the students said that the TikTok application had advantages in learning the descriptive text material. On the other hand, 13,64% of the students replied that the TikTok application did not give them many benefits in their learning. 63,64% of the students answered that they said the TikTok application helped them study the descriptive text. In contrast, 36,36% of the students answered that the TikTok application did not help in their studies. Last, 72,73% of the students had problems writing descriptive text using the TikTok application. However, 27,27% of them said they had no issues learning descriptive text using the TikTok application because they had mastered the materials.